2012 Frontiers in Education Conference Proceedings 2012
DOI: 10.1109/fie.2012.6462369
|View full text |Cite
|
Sign up to set email alerts
|

Work in progress: A comprehensive approach for mapping student's progress: Assessing student progress in freshman engineering

Abstract: A new method of assessment is developed that comprehensively maps students' progress in a course. The technique involves the use of two grading rubrics measuring performance in technical and conceptual proficiency, respectively. With these rubrics, one can identify students' progress and learning more effectively and future activities can be adapted accordingly. This paper discusses the development of these rubrics, how to use them, how to interpret their results, and describes an experiment showing their effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…We have further subdivided the inquiry stages into three states that we found the students to be in. These are : It is noteworthy that the student advances in learning and thinking stages [18][19][20][21][22][23][24] by going through the inquiry cycle multiple times. In every iteration the student grows and internalizes the cycle, creating new ideas and questions leading back to the process of inquiry.…”
Section: Dewey's Inquiry Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have further subdivided the inquiry stages into three states that we found the students to be in. These are : It is noteworthy that the student advances in learning and thinking stages [18][19][20][21][22][23][24] by going through the inquiry cycle multiple times. In every iteration the student grows and internalizes the cycle, creating new ideas and questions leading back to the process of inquiry.…”
Section: Dewey's Inquiry Methodsmentioning
confidence: 99%
“…One way to overcome many of these challenges is the inquiry-based learning approach [13][14][15][16][17]. In this technique the students can pursue their questions and inquiries by building on their preexisting knowledge.…”
Section: Reflective Practices and Inquiry: A Motivationmentioning
confidence: 99%
“…Students are afforded little to no space to communicate their personal thoughts with the faculty without significant effort on the part of the student or fear of retaliation. To overcome these barriers, an inquiry-based learning approach is taken [23], [24], [25], [26], [27]. This approach allows students to explore how they learn by providing a space to ask questions and build on their existing knowledge, further deepening their connections.…”
Section: Self-awareness: a Product Of Inquiry And Reflectionmentioning
confidence: 99%
“…The study also showed limitation of the tool for one segment of students. Similarly, studies [4,5] were also limited in their scope to freshman engineering students and first-year instructors. The study [5] performed showed some details but it is still under progress so detailed analysis is not available.…”
Section: Introductionmentioning
confidence: 99%